The Nigeria legal profession then, now and future; the changing natureand character of a profession (2017)
Recently there has been a growing concern over the unsavory conduct of some members of the legal profession and the falling standards of ethic in Nigeria and in many more jurisdictions the toga of integrity is being stripped from members of the profession, lawyers and judges alike. This paper examines the falling of ethical and professional standards in the Nigerian legal profession. the paper gives a brief expose on the history and development of the legal profession, the present decadence and corruptness, the negative impact and imminent threat , to the future of the profession in Nigeria. The paper posits that the falling standards and moral decadence is attributable to the long years of non- foundational teaching of legal ethics in the law faculties. This paper recommends the teaching of ethics in the foundational years of legal training, and a thorough review of the current curriculum and course content on the teaching of legal ethics using clinical legal education.